Comparison of two different intrathecal morphine doses for postoperative analgesia after video-assisted thoracoscopic surgery - Volkan Okbaz; Mediha Turktan; Ersel Gulec; Zehra Hatıpoglu; Cansu Bahcecı; Ismail C. Karacaoglu (Journal of Anaesthesiology Clinical Pharmacology)
Background and Aims: Postoperative pain is one of the most common problems after thoracic surgery. In this study, we aimed to investigate the analgesic effects of two different doses of intrathecal morphine (ITM) based on ideal body weight in patients who underwent video-assisted thoracoscopic surgery (VATS). Material and Methods: Forty-six patients scheduled for elective lung resection were included in this study. Patients were allocated to receive 10 μg/kg (Group I) and 7 μg/kg (Group II) ITM according to the ideal body weight for postoperative analgesia. Intraoperative and postoperative hemodynamic variables, postoperative morphine consumption, pain scores (at rest and effort), side effects, and additional analgesic requirements were recorded. Results: Postoperative pain scores did not differ in the first 12 h between the groups, but were significantly lower in Group I compared with Group II at 18 and 24 hours (P = 0.024 and P = 0.017 at rest, and P = 0.025 and P = 0.002 at effort, respectively). Postoperative morphine consumption was statistically significantly lower in Group I at all time periods (P < 0.05). The incidence of side effects was similar for both groups (P > 0.05). Conclusions: The use of 10 μg/kg ITM according to the ideal body weight provides more effective analgesia without increasing the side effects compared to 7 μg/kg ITM after VATS.